Resistensi Perempuan: Kajian Hegemoni Gramsei Dalam Novel "Sintren" Karya Dianing Widya Yudhistira - , AMRIN, S.S ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study object in this research is woman negotiation and resistance in Sintren novel. The research of resistance and woman negotiation uses Gramsci hegemony theory and feminist art criticism as formal object. Woman position which is subordination formed and deconstructed, either through culture or the subordinate position of woman is social. The differences of gender and sexes intend to be formed by capitalist and patriarchies of the existence of hegemony. Woman resistance happened due to the difference and inequality of gender in society. That phenomenon causes woman to do counter hegemony as struggle a form of to reconstruct woman position so that they get the justice of gender. Theoretically this research aims to express woman negotiation and resistance to ward patriarchy hegemony in Sintren novel. Practically, this research can give on the success of woman struggle in getting equivalence of gender such as those wanted by feminist clan. The conclusion of this research can be that the subordinate position of woman represents the result of patriarchy construction and capitalist either through cultural or social. The subordinate position of woman has an opportunity to dominate men, when woman can make good use of self potencies and intelligence. The opportunity especially woman to reconstruct their position will happen when she has strong bargaining position toward patriarchy domination. Woman struggle to go out from patriarchies hegemony and capitalist must be done collectively. Despitefully efficacy Womanâs bargaining position will peep out renegotiation from patriarchies. The success of woman negotiation and resistance must be supported by their awareness as an oppressed clan so that they will against their subordinate position collectively.